ChemInform Abstract: Catalytic Stereospecific Alkylation of Malononitriles with Enantioenriched Primary Allylic Amines. Issue 3 (21st January 2014) - Li, Man‐Bo; Li, Hao; Wang, Ju; Liu, Cong‐Rong; Tian, Shi‐Kai
Abstract The reaction proceeds with perfect retention of optical purity and alkene geometry.